Penerapan Ergonomi di Lingkungan Kerja pada UMKM Zo’ellen Sagela - Valentina Monoarfa; Arjan Gubali; Azhari Isima; Natalia; Dinarova Salsavia Datau; Febri Setiyawati; Nur Khairunnisa Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The application of ergonomics in the work environment of Micro, Small and Medium Enterprises (MSMEs) has an important role in increasing worker productivity, health and comfort. This research focuses on the MSME Zo'Ellen Sagela which produces a typical Gorontalo food, mashed sagela, and aims to examine the application of ergonomics in the production process. The research method used is descriptive qualitative, with data collection through observation and interviews. The research results show that an unergonomic work environment can cause physical complaints such as fatigue and work injuries, as well as reduce productivity. The application of ergonomic principles, such as adjusting work posture, arranging work tools, and efficient layout, can increase comfort and efficiency of the production process. Implementing proper ergonomics not only improves worker welfare, but also provides long-term benefits for business sustainability. Thus, the integration of ergonomics in the MSME work environment is a strategic step in creating a healthy, safe and productive work environment.